We start with:

-20=-20

16-36=25-45

We add 81/4 to sides of equation:

16-36+81/4=25-45+81/4

42-2*4*9/2+(9/2)2=52-2*5*9/2+(9/2)2

(22-9/2)2=(5-9/2)2

Square root of sides:

2*2-9/2=5-9/2

2*2=5

but why the result is this?

Results 1 to 4 of 4

- February 3rd 2010, 12:20 AM #1

- Joined
- Feb 2010
- Posts
- 10

- February 3rd 2010, 01:37 AM #2

- Joined
- Feb 2010
- Posts
- 10

- February 3rd 2010, 01:47 AM #3
Hello afsanehIt's when you take the square root that you need to be careful. Just because , it doesn't necessarily mean that . It could be that .

It is true that , the line I've coloured red. This is because, when we evaluate the expressions in each bracket, the one on the LHS is and the one on the RHS is . Squaring each of these gives the same answer: . But that doesn't mean that they are equal, does it?

So remember: when you take a square root, remember the possible minus sign!

Grandad

- February 3rd 2010, 02:42 AM #4

- Joined
- Feb 2010
- Posts
- 10